A Case of Langerhans Cell Histiocytosis With a Neck Mass as the First Symptom - Yuxin Xie; Xiaoming Kang; Xianlin Liu; Zhigan Wang; Qiancheng Jing (Clinical Case Reports)
ABSTRACT A 60‐year‐old female was found to have a mass in the neck and nasopharyngeal protrusion. These manifestations were highly prone to being misdiagnosed as cervical lymph node metastasis of nasopharyngeal carcinoma. The pathological examination confirmed LCH, a cell‐proliferative disease. Misdiagnosis should be avoided in clinical diagnosis.